Piqueteras - Bystrowicz, Malena.; Mastrosimone, Verónica.; Magud, Miguel.; Luzzani, Telma; Luzzani, Telma ([s. n.], 2002)
Documental que recorre la lucha de los desocupados en tres puntos claves del interior del país: .